(Since When) Are East and West German Business Cycles Synchronised? - Stefan Gießler; Katja Heinisch; Oliver Holtemöller (Jahrbücher für Nationalökonomie und Statistik, 2020)
We analyze whether, and since when, East and West German business cycles are synchronised. We investigate real GDP, unemployment rates and survey data as business cycle indicators and we employ several empirical methods. Overall, we find that the regional business cycles have synchronised over time. GDP-based indicators and survey data show a higher degree of synchronisation than the indicators based on unemployment rates. However, synchronisation among East and West German business cycles seems to have become weaker again recently.
Keywords: C32; E32; R11; 330; business cycles; synchronization; East Germany